2019
DOI: 10.1002/anie.201812184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydronium Ions in Zeolites on Sorption

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
172
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(194 citation statements)
references
References 32 publications
21
172
1
Order By: Relevance
“…This maximum water loading at operating conditions was estimated using an in‐house developed thermodynamic model for the adsorption of guest species in nanoporous materials . Furthermore, there is quite some experimental work available on how the water loadings depend on the acid site density, water vapor pressure and temperature in H‐ZSM‐5 and for which some interesting analogies can be found with our work . Secondly, as there is a high probability to find two silicon atoms in the next nearest neighbor position in SAPO materials, we introduced a second acid site in the unit cell, as was done in our earlier work .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This maximum water loading at operating conditions was estimated using an in‐house developed thermodynamic model for the adsorption of guest species in nanoporous materials . Furthermore, there is quite some experimental work available on how the water loadings depend on the acid site density, water vapor pressure and temperature in H‐ZSM‐5 and for which some interesting analogies can be found with our work . Secondly, as there is a high probability to find two silicon atoms in the next nearest neighbor position in SAPO materials, we introduced a second acid site in the unit cell, as was done in our earlier work .…”
Section: Introductionmentioning
confidence: 99%
“…[13,68] Furthermore, there is quite some experimental work available on how the water loadings depend on the acid site density, water vapor pressure and temperature in H-ZSM-5 and for which some interesting analogies can be found with our work. [69][70][71][72][73] Secondly, as there is a high probability to find two silicon atoms in the next nearest neighbor position in SAPO materials, we introduced a second acid site in the unit cell, [74,75] as was done in our earlier work. [36,52] Note that the schematic representation shown in Figure 2 corresponds to starting structures.…”
Section: Introductionmentioning
confidence: 99%
“…Ah igher Brønsted acidity was found for protons associatedw ith Si-O-Al linkages compared to those located at Al-O-Al linkages. As ac onsequence, the Si-O-All inkages were found to be deprotonated in AIMD simulations of hydrated models, leadingt ot he formation of protonated water clusters (= hydratedh ydronium ions [12] )i n the pores. Framework deprotonation was not observed for non-Lçwenstein linkages.…”
Section: Introductionmentioning
confidence: 90%
“…Ison and Gorte studied water adsorption on a HZSM‐5 with SAR = 70 via temperature programmed desorption (TPD), thermogravimetric analysis (TGA), and transmission infrared spectroscopy (IR), and found clusters of up to 5.3 waters per Al at 306 K. An adsorption energy of 12.1 kcal/mol and 8.2 kcal/mol was calculated for 0.7 and 2.0 waters per Al, respectively, leading to the conclusion that the first water forming a hydronium ion, H 3 O + , at the acid sites is more strongly held than subsequent waters that form clusters. Eckstein et al, also reported that water adsorption on HZSM‐5 is proportional to the Al content showing a maximum of 7 waters per Brønsted acid site …”
Section: Introductionmentioning
confidence: 99%